Technical Analysis of the Freestyle Stroke in the University Swimming Club - Raditya Pratama; Akbar Wibowo; Rahmad Hidayat; Via Diah Rohmana; Angga Indra Kusuma (International Journal of Sustainable English Language, Education, and Science, 2026)
From these various perspectives, it can be concluded that freestyle swimming is a fundamental swimming technique that is efficient and easier than other swimming styles, utilizing an arm-swinging motion over the water’s surface. To master these techniques, students must be self-motivated to improve their basic swimming skills. The purpose of this study is to determine the level of mastery of basic freestyle swimming techniques among students enrolled in the Swimming Course in the Physical Education, Health, and Recreation Program. This study is a descriptive study aimed at describing how to analyze the basic freestyle swimming techniques of students in the Swimming Club. The sampling technique used was purposive sampling, which involves selecting a sample based on specific criteria; in this study, the sample consisted of 30 students.  The overall results of the study, which involved 30 students from the Swimming Club at Cipta Wacana Christian University as the sample, showed that the level of mastery of freestyle swimming techniques was 67%, which is considered good, with an error rate of 33%.